FINANCING OF ORGANIC AGRICULTURE IN THE NORTH-EAST DEVELOPMENT REGION OF ROMANIA. A TERRITORIAL PROFILE ANALYSIS - Ioan Sebastian BRUMĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The North-East Development Region of Romania has a relatively longstanding history of practising organic agriculture. This paper introduces the way adopted by the farmers from this region, either they are certified or under conversion, for accessing the financing packages for organic agriculture within Measure 11 of National Programme of Rural Development (NPRD)2014-2020, in 2019. If we run a territorial profile analysis, there were requests for granting the compensatory aid for 81.17% of the organic agricultural area (certified or under conversion) in all six counties of the North-East Region. There are territorial differences within the region partly due to each county’s particularity along with the durable experience gathered in practising this type of agriculture. The analysis relies on the official data released by the Ministry of Agriculture and Rural Development (MARD) about the state of the areas utilized in organic system and, also by the Agency for Payments and Intervention for Agriculture (APIA) about accessing Measure 11 – Organic Agriculture in 2019.